Existence problems for homoclinic solutions. (19th February 2002) - Avramescu, Cezar
Abstract : The problemx ˙ = f ( t, x ),   x ( − ∞ ) = x ( + ∞ ), wherex ( ± ∞ ) : = lim t → ± ∞ x ( t ) ∈ ℝ n, is considered. Some existence results for this problem are established using the fixed point method and topological degree theory.